THE EFFECT OF SERVICE QUALITY AND PATIENT SATISFACTION ON PATIENT LOYALTY MEDIATED BY PATIENT TRUST AT RUMAH INDONESIA SEHAT (RIS) HOSPITAL - Fenny Kristinawati; Wani Devita Gunardi; Fushen (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The increasing number of hospitals and the development of health industry have resulted in competition between healthcare providers. In facing the inevitable competition in the health industry, healthcare providers are required to adjust and evolve to achieve higher standards. Things that can be done to face the demands of this market is improving the quality and patient satisfaction. The goal is to increase patient trust and loyalty. This research aims to determine the effect of service quality and patient satisfaction on patient loyalty mediated by patient trust at Rumah Indonesia Sehat (RIS) Hospital. There were 67 samples in this study. The data used in this study is a type of quantitative data obtained from filling out questionnaires by selected respondents through a simple random sampling method. The analysis method used in this study is the Structural Equation Model (SEM) using the SmartPLS program. The result of this study shows that there is a significant effect of service quality and patient satisfaction on patient loyalty with patient trust as an intervening variable.